Philanthropy in post-communist settings: strategic action or manifestation of social responsibility? - Vaidelytė-Tamulynienė, Eglė (Sociologija. Mintis ir veiksmas, 2004)
Together with the national Independence and the free market re-establishment, philanthropic tradition are returning back to the Lithuanian society. However philanthropy already appears in its modern qualities based not only on pure Christian morality, but also having some expressions of corporative social responsibility, strategic action. This paper is dwelling on the analysis of philanthropic phenomenon in post-communist settings revealing the dichotomy between philanthropy as social responsibility and its corporative strategic aspects. The analysis is based on interpretation of empirical and statistical data, as well as theoretical insights.